Education on stunting prevention using flipcharts: Building nutrition awareness in Kabba Village, Pangkep Regency - Walangadi, Zulkifli; Kalsum, Ummu; Azizah, Andi Nurul; Mentaruk, Indriani; Mappanyukki, Andi Atssam (Universitas Muhammadiyah Magelang, 2025)
Stunting is a critical public health issue characterized by linear growth in children below the normal standard, typically resulting from chronic malnutrition from the prenatal period up to the first two years of life. This community service program aimed to improve community knowledge regarding stunting prevention through balanced nutrition guidelines. The intervention utilized a social marketing approach employing flipchart media in Kabba Village, Pangkep Regency. The activity involved 25 participants (homemakers and community leaders) who attended interactive lectures facilitated by the flipchart media. The results demonstrate a significant knowledge gain: the proportion of participants categorized as having